The COVID-19 Pandemic Economic Implications in Iran: A National Survey Assessing Catastrophic Health Expenditures - Enayatollah Homaie Rad; Mohammad Hajizadeh; Shahrokh Yousefzadeh-Chabok; Fatemeh Keihanian; Vahid Yazdi-Feyzabadi; Leila Kouchakinejad-Eramsadati; Hedayat Salari; Atefeh Esfandiari; Hamed Zandian; Masoud Lotfizadeh; Hakimeh Mostafavi; Masoud Arefnezhad; et al. (Interdisciplinary Perspectives on Infectious Diseases, 2025)
Conclusion: The COVID-19 pandemic imposed an additional financial burden on households. The pandemic provided important lessons for health policymakers about the effectiveness of the health financing protection system during the crisis and the scarcity of health resources. Supply and demand of services are unbalanced in the outbreaks, and insurance systems might fall into failure due to the shortage of services, black markets, and price inflation.